Why Does Inulin have Pharmacological Activity? Theoretical Research by DFT and Concept DFT Methods - Long, Wei; Yuan, Yali; Li, Yuhui; Ma, Dandan; Wang, Xiaohua (Asian Journal of Chemistry, 2014)
The geometric structure optimization, frequency analysis, infrared spectroscopy, natural charge population, the natural bond orbital (NBO) analysis, the molecular and the frontier orbital energy are calculated about glucose, pyran-fructose, furfuran-fructose and inulin molecule by using density functional theory (DFT) method in B3LYP on the 6-311+g(d,p) basis set level. It is shown the stability order is: furfuran-fructose > pyran-fructose > glucose > inulin. We find that inulin's chemical potential is maximum, the chemical hardness is minimum and the electrophilicity index is maximum using the concept DFT method, which could account for it's pharmacological activity. The Fukui function scanning has shown the C2 atom in inulin molecule has strong electron-losing ability and it is the active center in the molecule. The EBDE calculation has shown the position of O2-–H is the most easily broken off and the bond energy is only 94.65 kcal mol-1, which is far less than the adiabatic ionization potential value, all of that could be a reasonable theoretical interpretation for the pharmacological activity of inulin.